(untitled) (KULT_online, 2015)
This work deals with time and imaginations of time during the 17th century and shows which fractions and developments can be observed during this period. Achim Landwehr, professor for Early Modern Ages at the University of Düsseldorf, explains that the meaning of time and its handling has changed since then. It was not a single imagination of time that dominated the Early Modern Period, but many competing models of time. Landwehr examines different sources to get closer to the phenomenon of time in the 17th century: Almanacs, clocks, newspapers and contemporary theories.